Inhibitory activities of selected South west Nigerian Medicinal (2013)
Tuberculosis (TB), an infectious disease prevalent in the tropics especially in Africa and Asia is one of the highest causes of morbidity and mortality and a global concern. With increasing resistance of the pathogen, to existing antituberculosis drugs and the synergy between TB infection and acquired immune deficiency syndrome (AIDS), the need for development of new drugs to cope with the infection is urgent.